Case of imported Vibrio cholerae O1 from India to South Africa - Ismail, Husna; Smith, Anthony M; Archer, Brett N; Tau, Nomsa P; Sooka, Arvinda; Thomas, Juno; Prinsloo, Ben; Keddy, Karen H (The Journal of Infection in Developing Countries, 2012)
This item has no abstract. Follow the link below to acccess the full text.